Deformation and recrystallization mechanisms inferred from microstructures of naturally deformed rock salt from the diapiric stem and surface glaciers of a salt diapir in Southern Iran. (April 2019) - Mansouri, Hadiseh; Prior, David J.; Ajalloeian, Rassoul; Elyaszadeh, Ramin
Abstract: Microstructures of three naturally deformed rocksalt samples, from the Deh Kuyeh salt fountain in South Iran, were studied by electron backscatter diffraction to constrain deformation and recrystallization processes. Two samples came from the upper salt fountain glaciers and one from the diapiric stem. Lattice distortion and low-angle boundaries in salt grains have intra-crystalline misorientations described by rotations around low-order crystallographic axes and are inferred to relate to dislocation creep and recovery. Misorientation analysis suggests that both easy and hard slip systems are responsible for grain distortions. Small grains have similar dimensions to subgrains, which we interpret to mean that subgrain rotation recrystallization (SGR) is important. Many boundaries are quite lobate, consistent with grain boundary migration (GBM) also being active. Bulges off of some large grains are related to the host by a tilt or twist boundary suggesting that GBM and SGR interacted to facilitate a bulge nucleation process. Idiomorphic grains occur, particularly in the upper fountain (surface glaciers) samples and are less deformed internally than neighboring grains. The grain and subgrain sizes in the sample from the diapiric stem are smaller than those in the upper salt fountain. Subgrain sizes suggest differential stresses were twice as large (2 MPa) during deformation in the diapiric stem compared to the upper fountain. The diapiric stem sample has greater intragranular distortion compared to the fountain samples. Furthermore, the diapiric stem sample has a continuous grain-boundary hierarchy, suggesting a dominance of SGR, whereas the upper fountain samples have different boundary hierarchy characteristics for boundary misorientations above and below ∼7° suggesting that GBM is limiting the SGR process: grains are consumed by GBM before boundaries with misorientations >7° developed by SGR. The increased importance of GBM relative to SGR in the upper fountain compared to the diapiric stem is consistent with the change in balance of the different recrystallization mechanisms expected as a function of lower stress magnitude in the upper fountain. Highlights: EBSD analysis was used to identify active deformation mechanisms during salt diapir emplacement. Subgrain rotation recrystallization is dominant in the upwelling stem of the salt diapir. Grain boundary migration is dominant in the glaciers at top of the fountain. Subgrain sizes suggest differential stresses are twice as large in the stem compared to the glaciers. Both primary and secondary slip systems are responsible for plastic deformation of salt grains.